Isokinetic quadriceps physiotherapy after knee surgery: a retrospective study - Nikolić, Siniša; Obradović, Borislav; Dimitrijević, Vanja; Rašković, Bojan; Dragičević-Cvjetković, Dragana (Frontiers in Rehabilitation Sciences, 2024)
Introduction: Quadriceps weakness after knee surgery is the most common consequence that can have different consequences for the knee itself, but also for the locomotor system in general. This research aimed to compare the results of isokinetic and isotonic exercise on torque restoration quadriceps on knee surgery. Methods: A sample of 180 subjects was analyzed, and divided into two subsamples to the type of rehabilitation treatment that was carried out. The examined group Aisokinetic consisted of 90 male subjects of age 28.54 ± 4.44 years. Their rehabilitation protocol was based on the isokinetic exercise of the quadriceps. The tested B-isotonic group consisted of 90 male subjects of age 27.93 ± 4.27 years. In these subjects, the rehabilitation protocol for strengthening quadriceps applied an exercise program with additional resistance, i.e. isotonic exercise in the gym. Before starting the rehabilitation treatment, an initial isokinetic test was performed at an angular speed of 60°/s in all subjects. After three and six weeks of rehabilitation treatment, control tests were performed in the same way as in the initial test. Results: Based on the values of MANOVA analysis and discriminative analysis, significantly better results of isokinetic tests were found in the examined group A-isokinetic compared to the examined group B-isotonic. At the final measurement of Group A, 83 respondents (92.2%) were placed in the "biggest" class out of a total of 90 respondents.Based on the obtained research results, we conclude that isokinetic exercise is more effective in terms of physiotherapy of quadriceps hypotrophy after knee surgery.